2015
DOI: 10.5897/ijnam2015.0187
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in factors associated with overweight and obesity among civil servants in Lagos, Nigeria

Abstract: Overweight and obesity constitute global public health problems with consequences on health and productivity of workers. This study was designed to describe the gender variation in the factors associated with overweight, obesity and hypertension among civil servants in Lagos, Nigeria. This comparative cross-sectional study was conducted in 280 civil servants recruited from seven local government areas in Lagos state using random sampling technique. A pre-tested, intervieweradministered questionnaire was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
3
2
0
Order By: Relevance
“…In this study, a majority of the participants were overweight and obese (79.9%), and it indicated that an alarming sign of higher prevalence of obesity. It was consistent with the previous studies [29, 30] where more than half of their civil servants screened were obese. It indicated rapid urbanization and adaptation of more sedentary lifestyle leading to unhealthy outcomes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, a majority of the participants were overweight and obese (79.9%), and it indicated that an alarming sign of higher prevalence of obesity. It was consistent with the previous studies [29, 30] where more than half of their civil servants screened were obese. It indicated rapid urbanization and adaptation of more sedentary lifestyle leading to unhealthy outcomes.…”
Section: Discussionsupporting
confidence: 93%
“…Chai and Chee [31] in their study reported that 4 out of 15 subjects manifested with high visceral fat accumulation. Consistent with the literature, the finding reported that visceral fat percentage of men was higher (12.7%) than women (9.1%), similar to the results of the study conducted by Ajani et al [30]. …”
Section: Discussionsupporting
confidence: 91%
“…Overweight and obesity were found in more than half of the study population and was associated with increasing age and income. The prevalence rate of overweight and obesity among civil servants in Oyo State (57.3%) is similar to the rates reported among civil servants in Kaduna [ 5 ] and Abakaliki [ 32 ] but is much lower than the rate in Lagos (70.7%) which has higher socio- economic status [ 38 ]. The occurrence of overweight and obesity is partly attributable to the sedentary nature of civil service work [physical inactivity (OR = 3.82)], which is usually associated with prolonged hours of sitting, minimal energy expenditure, snacking on energy-dense foods, including sugar-sweetened beverages, and infrequent consumption of homemade foods.…”
Section: Discussionsupporting
confidence: 65%
“…The occurrence of overweight and obesity is partly attributable to the sedentary nature of civil service work [physical inactivity (OR = 3.82)], which is usually associated with prolonged hours of sitting, minimal energy expenditure, snacking on energy-dense foods, including sugar-sweetened beverages, and infrequent consumption of homemade foods. Prolonged hours of sitting has been associated with increased risk of raised blood sugar, cardiovascular diseases, and cancers [ 38 40 ]. Besides, fast food or restaurant prepared meals are usually calorie-dense with high levels of sugar, salt and oils to enhance the taste and induce people, for profit reasons, to consume portions in excess of their needs.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity during adolescence has health consequences in adulthood, such as type 2 diabetes, insulin resistance, dyslipidemia, hypertension, severe obesity, renal dysfunction and limited mobility [10,11]. Although genes predispose an individual to obesity, so many other factors have been reported to be responsible for the increasing epidemic of obesity, among these are socio-demographic factors [12,13] and changing society, as well as the communities behavioral pattern, brought about by economy dynamics, modernization, urbanization, and globalization of food market [14,15]. As such, giving rise to preference of consuming energy-dense foods and decreased physical activity patterns, and as a consequence, energy imbalance that may result in obesity ensues [14].…”
Section: Introductionmentioning
confidence: 99%